2004
DOI: 10.1002/ijc.20449
|View full text |Cite
|
Sign up to set email alerts
|

Combination of low‐dose cisplatin and recombinant xenogeneic endoglin as a vaccine induces synergistic antitumor activities

Abstract: Angiogenesis is critical to the growth and metastasis of solid tumors, and acquired drug resistance is one of the major hindrances to chemotherapy. Thus, we sought a rational strategy using the combination of antiangiogenic biotherapy and chemotherapy for cancer therapy. We explored the efficacy of a strategy combining low-dose cisplatin and a recombinant xenogeneic endoglin as a protein vaccine, which we previously demonstrated to have effective antiangiogenic effects in several mouse models. We found that bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…After tumors had grown for 7 days, the mice were randomly divided into four groups (10 mice/group) for treatments according to similarly described procedures. 42 . At the end of the experiment, the mice were killed and their tumor tissues were collected for subsequent histological experiments (see below).…”
Section: Animal Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…After tumors had grown for 7 days, the mice were randomly divided into four groups (10 mice/group) for treatments according to similarly described procedures. 42 . At the end of the experiment, the mice were killed and their tumor tissues were collected for subsequent histological experiments (see below).…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Digital images were acquired and processed using Adobe Photoshop (Adobe Inc., Mountain View, CA, USA), and were quantified as described previously. 42 …”
Section: Quantitative Assessment Of Apoptosismentioning
confidence: 99%
“…Several recent studies comparing the efficacy of chemotherapy at high and low doses in combination with antiangiogenic drug documented the longest survival in animals that received low-dose chemotherapy and antiangiogenic treatment. This was associated with no side effects and a marked decrease in tumor size (19)(20)(21). However, there are no reports that address the therapeutic and immunomodulating potential of lowdose chemotherapeutic agents in a setting of combined chemotherapy with cancer vaccines.…”
mentioning
confidence: 99%
“…The main function of CDDP is to damage DNA and induce apoptosis (24,25). Although CDDP is not thought to inhibit angiogenesis specifically, some researchers have reported that CDDP provided antiangiogenic effects against several human and mouse cancer cells, including Colon26 carcinoma (26,27). In addition, the larger vessels in the outer area of tumor are less affected by the antiangiogenic therapy, but small vessels perfused in the tumor are more sensitive to the therapy (1,28,29).…”
Section: Discussionmentioning
confidence: 99%